2020
DOI: 10.3390/ijerph17197341
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Compliance Behaviors among Middle-Aged and Older Hypertensive Patients in China: Results from the China Health and Retirement Longitudinal Study

Abstract: Partial or total non-adherence has been recognized as major issues in the long-term management of hypertension. This study aims to investigate the prevalence and associated factors of compliance behaviors among Chinese middle-aged and older hypertensive patients. A sample of 6308 hypertensive patients aged ≥45 years was obtained from the 2015 China Health and Retirement Longitudinal Study (CHARLS) data. Two compliance behaviors were involved including medication and blood pressure monitoring. Stratified binary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
(25 reference statements)
2
9
0
Order By: Relevance
“…In various settings, improved medicine accessibility through FCPEM programs proved to help reduce patients' direct medical costs and possibly lead to increased patient participation, continuity of treatment, and better health outcomes [15,[24][25][26][27]. Furthermore, we found that patients with characteristics indicative of free medicine use in our study coincided with patients who had chronic illnesses and poor medicine use and adherence in previous studies [28][29][30]. This implies that FCPEM implementation can promote equitable access to medicines and improve the health outcomes of vulnerable populations.…”
Section: Discussionsupporting
confidence: 66%
“…In various settings, improved medicine accessibility through FCPEM programs proved to help reduce patients' direct medical costs and possibly lead to increased patient participation, continuity of treatment, and better health outcomes [15,[24][25][26][27]. Furthermore, we found that patients with characteristics indicative of free medicine use in our study coincided with patients who had chronic illnesses and poor medicine use and adherence in previous studies [28][29][30]. This implies that FCPEM implementation can promote equitable access to medicines and improve the health outcomes of vulnerable populations.…”
Section: Discussionsupporting
confidence: 66%
“…The result was in agreement with some earlier studies. 16 , 22 , 23 This was explained by the high gap in socio-economic, cultural and education aspects between urban and rural areas in China. Economic status was one of the factors affecting adherence of hypertensive patients and lack of financial resources was a major barrier to adherence 24 .…”
Section: Discussionmentioning
confidence: 99%
“…First, it is necessary to change our ideas and reshape our cognition. As the initiating factor of disability risk in the older population, population aging is the current trend ( 68 ), and the risks and challenges it brings are global ( 69 ), long-term ( 70 ), and irreversible ( 71 ). Therefore, in the face of the challenge of social disability risk, we must abandon the unsuitable concepts of “partial war,” “quick decision war,” and “temporary war.” This is an inevitable historical turning point in the development of human society from the perspectives of both the evolution of research disciplines and our understanding of the causes of aging.…”
Section: Discussionmentioning
confidence: 99%
“…First, it is necessary to change our ideas and reshape our cognition. As the initiating factor of disability risk in the older population, population aging is the current trend (68), and the risks and challenges it brings are global (69), long-term (70), and irreversible (71). Therefore, in the face of the challenge of social disability risk, we must abandon the unsuitable concepts of "partial war, " "quick decision war, " and "temporary war."…”
Section: Figurementioning
confidence: 99%